Sucrose-Mediated Fast Synthesis of Zinc Oxide Nanoparticles for the Photocatalytic Degradation of Organic Pollutants in Water - Islam, Md (2019)
We report a facile method for the synthesis of zinc oxide nanoparticles (nZnOs) by rapidly heating a paste of zinc nitrate and sucrose on the hot plate at 500 °C. The transmission electron microscopy images revealed the spherical shape of the ZnO with an average size of 35 nm. The band gap and the specific surface area of the nZnO were measured to be about 3.32 eV and 80.11 m2/g, respectively. The nZnO was utilized for the photocatalytic degradation of methyl orange (MO) and methylene blue (MB) in water under the ultraviolet (UV-B) light and sunlight irradiation. Photocatalysis was performed in two types of water matrices, viz., the deionized water and the simulated fresh drinking water. Almost a complete degradation of MO and MB was obtained within 30 min of UV-B light irradiation. Under sunlight irradiation, more than 95% of the MO solution underwent degradation within 30 min. The photocatalytic stability of the nZnO was examined for five cycles, and a similar activity was found throughout the cycles. The photocatalytic generation of the hydroxyl radical (•OH) was confirmed by the terephthalic acid photoluminescence tests. Moreover, the synthesis methodology was validated by triplicating the nZnO synthesis. Every time, the ZnO demonstrated a similar photocatalytic activity, which confirmed the robustness of the synthesis procedure.